DEVELOPMENT OF LEARNING GUIDANCE AND COUNSELING - Rifqi Muhammad (Cross-border, 2020)
This paper aims to describe the development of learning guidance and counseling. The development of tutoring for counselees is carried out with the following efforts, namely: Introduction of Psychological Learning Difficulties; Disclosure of Counselees' Learning Problems or Difficulties; Counseling Learning Difficulty Solving Assistance; Increasing Counselee's Learning Motivation; Development of Good Study Attitudes and Habits; Improving the Counselor's Learning Skills; and Service Delivery Improvement Program